RESEARCH OF BETA AS ADEQUATE RISK MEASURE-IS BETA STILL ALIVE? - Ante Perković (Croatian Operational Research Review, 2011)
The capital asset pricing model (CAPM) is one of the most important models in financial economics and it has a long history of theoretical and empirical investigations. The main underlying concept of the CAPM model is that assets with a high risk (high beta) should earn a higher return than assets with a low risk (low beta) and vice versa. The implication which can be drawn out of this is that all assets with a beta above zero bear some risk and therefore their expected return is above the return of the risk-free rate. In this research observation on monthly stock prices on Croatian stock market from January 1st 2005 until December 31st 2009 is used to form our sample. CROBEX index is used as proxy of the market portfolio. The results demonstrate that beta can not be trusted in making investment decisions and rejects the validity of the whole CAPM model on Croatian stock market.